2016
DOI: 10.3892/etm.2016.3000
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral T-lymphocyte and natural killer cell population imbalance is associated with septic encephalopathy in patients with severe sepsis

Abstract: Abstract. Septic encephalopathy (SE) is a diffuse cerebral dysfunction resulting from a systemic inflammatory response, and is associated with an increased risk of mortality. The pathogenesis of SE is complex and multifactorial, but unregulated immune imbalance may be an important factor. The current retrospective study examined the clinical data of 86 patients with severe sepsis who were admitted to the Intensive Care Unit at Zhongshan Hospital, Xiamen University (Xiamen, China) from January, 2014 to January,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 63 publications
(57 reference statements)
0
9
0
Order By: Relevance
“…Our study reveals the significance of seasonality in predicting adverse postoperative outcomes in bariatric surgeries and thus provides evidence to help the decision making about the timing for these elective surgeries. For patients with elevated risks for DVT complications (e.g., chronic heart failure, long hours of physical inactivity, history of multiple pregnancies, or rheumatoid arthritis [27,40]) and sepsis (e.g., older age, immune system impairment, chronic or serious illness [41,42]), such precautionary awareness of the possible seasonality factor could be particularly important. On the other hand, because the crude rate for DVT was only .16%, the clinical implication of those statistically significant ORs we estimated might be limited.…”
Section: Discussionmentioning
confidence: 99%
“…Our study reveals the significance of seasonality in predicting adverse postoperative outcomes in bariatric surgeries and thus provides evidence to help the decision making about the timing for these elective surgeries. For patients with elevated risks for DVT complications (e.g., chronic heart failure, long hours of physical inactivity, history of multiple pregnancies, or rheumatoid arthritis [27,40]) and sepsis (e.g., older age, immune system impairment, chronic or serious illness [41,42]), such precautionary awareness of the possible seasonality factor could be particularly important. On the other hand, because the crude rate for DVT was only .16%, the clinical implication of those statistically significant ORs we estimated might be limited.…”
Section: Discussionmentioning
confidence: 99%
“…Failure to maintain homeostasis between Th1 and Th2 cells might be a major indicator of immune system dysfunction under septic conditions [89]. Depletion of peripheral T lymphocytes is independently associated with the development of SAE, as reported by Lu and colleagues [92]. Similarly, the types of T cells and their polarization status accounts for sepsis-induced brain injury and should be taken into consideration for effective treatments [93].…”
Section: T Cellsmentioning
confidence: 90%
“…On the other hand, Boomer et al [19] and Holub et al [20] had reported decreased number of NK cells in the blood of patients at 24 h after the onset of sepsis. This phenomenon was thought to be related to the increased incidence of secondary infection [21] and sepsis encephalopathy [22]. The multi-faceted effects of NK cells have led to contradictory outcomes in patients with sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Twentyeight patients had nosocomial infections, and 41 patients had septic shock. APACHE II scores (22 [15][16][17][18][19][20][21][22][23][24][25][26] vs.15 [10][11][12][13][14][15][16][17][18][19][20][21][22], p = 0.003), SOFA scores (9 (6-13) vs. 6 (4-9), p < 0.001), lactate level (2.5 (1.7-4.0) mmol/L vs. 1.5 (1.1-2.5) mmol/L, p = 0.002), and positive rate of bloodstream infection (16.7% vs. 4.8%, p = 0.038) were significantly higher in the non-survivors than the survivors. However, the Glasgow Coma Scale (GCS) scores showed the opposite trend between the two groups (7 (6)(7)(8)(9)(10)(11)(12)(13)(14) vs.14 (8)(9)(10)(11)(12)(13)(14)(15), p = 0.007).…”
Section: Patient Characteristicsmentioning
confidence: 99%